(untitled) (Research, Society and Development, 2021)
Anhydrobiosis refers to a state of suspended animation in which some organisms enter when exposed to extreme desiccation, ensuring them an outstanding tolerance to several physical stresses due to molecular and cellular adaptations. Metallothioneins (MTs) are short cysteine-rich metal-chelating proteins that work as a cellular protection element in metal ion-rich conditions. Here we aimed to investigate possible molecular signatures in primary and tertiary structures in anhydrobiotic cyanobacterial MTs. Anhydrobiotic and non-anhydrobiotic cyanobacterial MT amino acid sequences were retrieved from NCBI database and aligned in Clustal Omega server. Additionally, the amino acid compositions of these sequences were determined by GeneRunner. Further, we carried out homology-modeling via SWISS-MODEL, structural superposition in UCSF Chimera 1.4 Matchmaker tool and ligand-binding site prediction via COFACTOR. In silico analyses revealed specific divergences in amino acid positions between MT groups, evidencing positive and negative selections, however without affecting final protein structures. Some of these changes on polypeptide sequence potentially enhance protein stabilization during desiccation, whereas others possibly act as additional metal-ion coordinating residues. Analyses on the molecular adaptations on anhydrobiotic cyanobacterial MTs help shed light on their molecular functions and biological roles, as well as may have applications on the development of desiccation- and metal-tolerant organisms.